The Role of Single Parents in Enhancing Children's Learning Motivation: A Case Study at Islamic Elementary School - Erisa Widya Putri; Siti Nurjanah; Ifrohan Ifrohan (Journal of English Language and Education, 2026)
The family is the first environment that plays an important role in shaping children's learning motivation, including families with a single parent due to the death of a spouse. This condition requires a single parent to perform dual roles as both caregiver and breadwinner, making it important to examine how single parents contribute to enhancing children's learning motivation. This study aimed to describe the role of a single parent in improving the learning motivation of a second-grade student at MI Islamiyah Tugu Agung, the obstacles encountered, the child's responses, and the strategies employed. This research used a qualitative approach with a field research method. Data were collected through observation, in-depth interviews, and documentation. The primary data sources were Mrs. K as a single parent and her child, R, while secondary data were obtained from school documents and relevant literature. The findings revealed that Mrs. K acted as an emotional supporter and learning motivator by providing attention, affection, learning assistance, communication with teachers, and praise and rewards. Despite facing limited time, economic pressure, and physical and emotional fatigue, these efforts succeeded in improving R's discipline, enthusiasm, and academic achievement. Therefore, the role of a single parent can effectively support and enhance children's learning motivation.